AERODYNAMIC HIGH-RISE BUILDING IN STRUCTURAL REVIEW AND DESIGN INTEGRATION - Nugrahini, Fibria Conytin (Border: Jurnal Arsitektur, 2024)
Tall buildings that have aerodynamic characteristics are tall buildings that can respond to wind flow and lateral loads that occur on the upper structure of the building. Obstacles in understanding the structural systems in tall buildings often become obstacles for architecture students so design integration cannot be achieved, especially in tall buildings with aerodynamic shapes. Therefore, it is necessary to analyze how the structural patterns that form aerodynamic buildings can be realized using case studies in Indonesia and abroad. The method used in this research is a literature review and analysis with a review of aerodynamic building designs and structures in three building case studies in Indonesia and abroad. It is hoped that by understanding aerodynamic building structural systems, students will be able to combine creativity with their structural systems. Conversely, understanding the structural system can produce design creativity to create an integration of the design and structural system. From the literature review and analysis, it is found that aerodynamic tall buildings have a structural system obtained from twister-shape processing with a composite structural system and a core system. As well as the diagrid system which usually uses a steel diagrid structure system and a core structure system. The core system is still the main reference because its use is more efficient in terms of costs and work methods.